Website-Based School Financial Information System - Takhrisna Amila Alfaida; Utami, Syefti Rahma; Febikhanaya Putri; Hidayatur Rakhmawati; Alma Fatikhul Khak; Muhammad Dafie Ardiansyah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of information technology has brought significant changes in data and information management in the educational environment. This research focuses on the development of a website-based Financial Information System tailored to the needs of SDIT Binaul Izzah Bumiayu. This system was designed using the waterfall method with stages of needs analysis, design, implementation, and testing to improve efficiency, accuracy, and ease in managing school financial data which was previously still manual. The results of the study indicate that the system created is able to assist schools in the process of recording, recapitulating financial reports, and accelerating data access while reducing human error. Recommendations for future system development include the addition of payment notification features, automatic reports, student data integration, improvement of supporting facilities, and ongoing cooperation between schools and universities, followed by periodic evaluations to improve system quality.